A Peaking and Tailing Approach to Education and Curriculum Renewal for Sustainable Development - Desha, C.; Hargroves, Charlie (Adver, SUSTDE, 2014)
Contextual factors for sustainable development such as population growth, energy, and resource availability and consumption levels, food production yield, and growth in pollution, provide numerous complex and rapidly changing education and training requirements for a variety of professions including engineering. Furthermore, these requirements may not be clearly understood or expressed by designers, governments, professional bodies or the industry. Within this context, this paper focuses on one priority area for greening the economy through sustainable development—improving energy efficiency—and discusses the complexity of capacity building needs for professionals. The paper begins by acknowledging the historical evolution of sustainability considerations, and the complexity embedded in built environment solutions. The authors propose a dual-track approach to building capacity building, with a short-term focus on improvement (i.e., making peaking challenges a priority for postgraduate education), and a long-term focus on transformational innovation (i.e., making tailing challenges a priority for undergraduate education). A case study is provided, of Australian experiences over the last decade with regard to the topic area of energy efficiency. The authors conclude with reflections on implications for the approach.